DEVELOPMENT OF «LIABILITY INSURANCE» IN GEORGIA FOR THE LAST 10 YEARS» (OVERVIEW OF 2008 - 2018) - Bregvadze Roland (ეკონომიკური პროფილი, 2020)
The article discusses the development prospects of liability insurance in Georgia as a field, discusses various statistical data on insurance products for 2008-2018, including liability insurance, makes comparative analysis, discusses the example of advanced countries in terms of liability insurance development, discusses problems and future prospects of liability insurance for development